Social Media Impact on Reading Comprehension among Filipino Learners: A Systematic Review - Ermita, Lota G; Gabor, Edward Francis; Bambico , Froilan H.; Ocasla, Vicenta M.; Borja, Joanna A. De (Edu Berkah Khatulistiwa, 2025)
This systematic review explores the impact of social media on reading comprehension among Filipino learners, addressing a growing concern as social media becomes more integrated into students' daily lives. With the Philippines ranking among the top countries for social media usage, this study consolidates findings from various research to understand how these platforms affect students' ability to comprehend and process text. The review highlights both positive and negative influences. On one hand, excessive social media use is associated with reduced attention spans, fragmented reading habits, and cognitive overload, all of which hinder deep reading and comprehension. On the other hand, when social media is used for educational purposes—such as online discussions, collaborative learning, and sharing of academic content—it can enhance student engagement and improve comprehension skills. Despite these findings, the literature is lacking, particularly regarding the long-term effects of social media on younger learners and the role of different platforms. This review concludes with recommendations for future research and suggests strategies for educators to harness social media's educational benefits while mitigating its distractions.